2017
DOI: 10.1097/wnr.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen inhalation attenuates postoperative cognitive impairment in rats

Abstract: Postoperative cognitive decline is a major clinical problem with high morbidity and mortality after surgery. Many studies have found that molecular hydrogen (H2) has significant neuroprotection against acute and chronic neurological injury by regulating inflammation and apoptosis. In this study, we hypothesized that H2 treatment could ameliorate the development of cognitive impairment following surgery. Adult male rats were subjected to stabilized tibial fracture operation under anesthesia. Two percent of H2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In our previous report, maternal H 2 administration reduced both the excessive microglial activation and the increased IL-6 levels in the MIA fetal brains 12 , which could ameliorate the behavioral deficits later in life. Previous studies in adult rodents reported that H 2 treatment could mitigate the behavioral dysfunctions, including short-term memory deficits, cognitive impairments, and depressive-like behaviors, by regulating inflammation and ROS production 67 , 68 , which is in line with our current results. Moreover, the present study demonstrated that prenatal H 2 administration restored the MIA-induced neuronal and oligodendrocytic loss, and suppressed the excessive activation of astrocytes at postnatal 5 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…In our previous report, maternal H 2 administration reduced both the excessive microglial activation and the increased IL-6 levels in the MIA fetal brains 12 , which could ameliorate the behavioral deficits later in life. Previous studies in adult rodents reported that H 2 treatment could mitigate the behavioral dysfunctions, including short-term memory deficits, cognitive impairments, and depressive-like behaviors, by regulating inflammation and ROS production 67 , 68 , which is in line with our current results. Moreover, the present study demonstrated that prenatal H 2 administration restored the MIA-induced neuronal and oligodendrocytic loss, and suppressed the excessive activation of astrocytes at postnatal 5 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…Recent findings suggest that H 2 treatment is neuroprotective in patients with cerebral I/R injury [ 54 ]. H 2 also mitigates surgery-induced cognitive impairment [ 55 ], decreases lung graft injury [ 56 ] and radiation-induced skin injury in rats [ 57 ], and attenuates lipopolysaccharide-induced acute lung injury in mice [ 14 ].…”
Section: H 2 Delivery Mechanismsmentioning
confidence: 99%
“…Previous studies have shown that hydrogen therapy could improve neurological outcome in animal models of ischemic and hemorrhagic cerebral stroke (Zhan et al, 2012;Zhuang et al, 2012;Shao et al, 2016;Wang et al, 2016;Ono et al, 2017). Hydrogen inhalation can attenuate postoperative cognitive impairment by regulating inflammation and apoptosis in a rat model (Xin et al, 2017). However, long-term outcomes following hydrogen inhalation after SAH has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen (H 2 ) was administered to experimental rats by inhalation, which was started 0.5 h after the induction of SAH. Hydrogen administration was performed following procedures described in a previous study (Xin et al, 2017). Thus, rats were placed in a transparent chamber that had an inlet connected with 3.3% hydrogen gas inhaler (MIZ, MHG-2000, Japan).…”
Section: Hydrogen Administrationmentioning
confidence: 99%